2021
DOI: 10.1136/bcr-2020-239457
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 IgG-related autoimmune inflammatory necrotizing myositis

Abstract: The COVID-19 pandemic caused by the SARS-CoV-2 virus has affected millions of people around the globe. The most common presentation of COVID-19 is fever and upper and lower respiratory tract infection. Myalgia is fairly common in the prodromal phase of the viral illness which self-resolves. There is very scant literature on autoimmune myositis triggered by COVID-19 infection. We report a case of SARS-CoV-2 infection, who presented with progressive muscle weakness with rhabdomyolysis and necrotizing autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Therefore, 9 cases from 8 articles were included in this review. Six cases fulfilled the 2017 EULAR/ACR classification criteria for adult and juvenile IIM and 3 patients were classified as possible polymyositis according to the Bohan and Peter criteria for DM and PM [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ] ( Supplementary file ). Four cases were reports from Europe, 3 from America, and 2 from Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 9 cases from 8 articles were included in this review. Six cases fulfilled the 2017 EULAR/ACR classification criteria for adult and juvenile IIM and 3 patients were classified as possible polymyositis according to the Bohan and Peter criteria for DM and PM [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ] ( Supplementary file ). Four cases were reports from Europe, 3 from America, and 2 from Asia.…”
Section: Resultsmentioning
confidence: 99%
“…SARS‐CoV‐2 infection‐associated myopathy may be an immune‐mediated necrotizing myopathy, unspecified necrotizing myopathy or myositis. 12 , 13 , 14 SARS‐CoV immunostaining of skeletal muscle was performed in 2 recently reported autopsy studies, and negative possibly due to postmortem changes with a postmortem interval of up to 6 days, 13 , 14 although positive SARS‐CoV‐2 testing by reverse transcription quantitative PCR (RT‐qPCR) was found in at least 16% (7/41) of quadriceps and 5% (2/42) of deltoid muscles. 14 Our present study (with the muscle biopsy tissue processed in 0.5 day) is the first to demonstrate SARS‐CoV+ myofibers with granular staining and EM finding of virus‐like particles consistent with SARS‐CoV‐2, which suggests direct viral infection of the muscle in some patients with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of necrotizing myositis was established after muscle biopsy [ 3 ]. Another similar study reported a case in which the patient presented with worsening dyspnea and elevated CK 1 month after COVID-19 infection, but the lower extremity weakness started after 3 months [ 26 ]. These studies are all similar to our report, in which the patient presented with increased CK and acute lower extremity weakness weeks after the initial COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%